2006
DOI: 10.1152/ajpcell.00626.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and invasiveness of metastatic esophageal cancer are potentiated by shear stress in a ROCK- and Ras-dependent manner

Abstract: To metastasize, tumor cells must adopt different morphological responses to resist shear forces encountered in circulating blood and invade through basement membranes. The Rho and Ras GTPases play a critical role in regulating this dynamic behavior. Recently, we demonstrated shear-induced activation of adherent esophageal metastatic cells, characterized by formation of dynamic membrane blebs. Although membrane blebbing has only recently been characterized as a rounded mode of cellular invasion promoted through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 34 publications
6
40
0
Order By: Relevance
“…(16) In the current investigation we describe a novel role for shear in the internalization of E-cadherin. Specifically we show that: (1) venous shear induces the internalization of E-cadherin from cell-cell junctions into Rab5-positive endosomes; (2) Src inhibition disrupts shear-induced internalization of E-cadherin; and finally that (3) sheared OC-1 cells invade in a Src-dependent manner.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…(16) In the current investigation we describe a novel role for shear in the internalization of E-cadherin. Specifically we show that: (1) venous shear induces the internalization of E-cadherin from cell-cell junctions into Rab5-positive endosomes; (2) Src inhibition disrupts shear-induced internalization of E-cadherin; and finally that (3) sheared OC-1 cells invade in a Src-dependent manner.…”
Section: Discussionmentioning
confidence: 87%
“…Previously, we (16) and others (4) have shown that exposure to shear causes activation, translocation, and clustering of integrins in tumor cells; however, it is unknown if shear induces rearrangement of adherens junctions, in particular, the cadherins in adherent metastatic cells. Because Fn supports maximal adhesion of OC-1 cells under venous fluid flow, (16) we used Fn as the adhesive matrix component in all parallel plate flow experiments. A period of 30 min enabled maximal interactions of OC-1 cells with Fn.…”
Section: Venous Shear Reduces Cell-cell Contacts Between Oc-1 Cells Amentioning
confidence: 94%
See 1 more Smart Citation
“…Lawler et al [97] have also shown that mobility and invasiveness of metastatic esophageal cancer cells are potentiated by shear stress through the Rho kinase (ROCK) and Rassignaling pathways, suggesting a novel physiological role for Rock and Ras in metastatic behavior of cancer cells [97].…”
Section: Ras Signalingmentioning
confidence: 99%
“…The proposed mechanism would thus be relating and combining the mechanical inputs to the biological outputs, in conjunction with the activity regulation of the Ras protein by the mechanical terms such as the shear force [260] and the plasma membrane viscosity [261]. The shear stress within the body, generated by the cardiac cycle and experienced by the endothelial cells, was given as a function of blood flow patterns throughout the vasculature [262].…”
Section: Significance Of the Mechanism;mentioning
confidence: 99%